The Meaning, Benefit and Importance of Development Entrepreneurship in Higher Education - Erlangga, Heri (Asian Journal of Contemporary Education, 2019)
This paper based on qualitative research to understanding of the meaning, benefit and importance of entrepreneurship that develops in the environment of higher education. This research using qualitative research with a naturalistic inquiry approach. This approach was chosen because it was considered more suitable with the characteristics of the problem under study, namely with regard to Entrepreneurship behavior. Data collection of information using facts is done by research techniques such as interviews and participant observation. Result of the study found that teaching about entrepreneurship in higher education in the area of practical approaches (practical concepts or psychomotor aspects in the meaning of learning). Indeed, the meaning of entrepreneurship should have a 'spirit' from the start of scientific concepts, concepts of attitude and practical concepts. This study also found that meaning entrepreneurship is important to step development to improve the benefit of entrepreneurship. The benefits of developing entrepreneurship can provide a spirit to the academic community that many campuses are successful and successful because management has the ability to think creatively and inventively. Works and initiatives are only found in campus management which consists of people who think creatively. Not a few campuses have succeeded because they have creative and innovative abilities.